A methods engineering study on Super Industrial Corporation - Lanquino, Melanie (College of Engineering, 2005)
This paper is a methods engineering study on Super Industrial Corporation. Super Industrial Corporation is a manufacturing company that produces black and galvanized steel pipes and couplings. Essentially they produce steel pipes in various sizes ranging from 15 mm-200 mm in its inner diameter. The steel pipes also come in two forms in accordance to its proper utilization-light gauge for regular industrial steel pipe purposes and the heavy gauge are for the more intense inner pressure. The company also ventures in the production of light gage structurals and also undertakes projects-production of school houses, low-cost houses, and school armchairs and desks. This paper discusses the problems encountered in the company and proposes recommendations along with implementations that would help the company improve its productivity and worker efficiency through better working conditions. The operations in the said company are highly mechanized. The manufacturing of the product is in essence produced with the raw materials being formed through the machines and only a modest amount of worker supervision. The layout is not an eminent source of improving the operations since the flow of production is basic and the current arrangement suits well the needs of the company. It should be noted too that it is quite prominent in almost every area that the workstations are quite messy. Workers experience hot temperature conditions in the working areas. Air ventilation is not sufficient and this can easily be noted by the lack of means in the production area. The main problem is attributed to the failure of coping up with the technological advancements of the machineries that the operations need. Most of the problems with the production are due to machine breakdowns and part breakups of the old machines. It must be noted too that the machines during the start of its production in the 60's are still the ones being used and some of the repairs and maintenance of the company has resorted to using alternative parts just to keep the machines on the go for production. This problem is really important to note out since the production heavily relies on the work of the machineries. The major proposed recommendation is really costly since it'll be on the core of buying new machinery for the production. Due to budget constraints by the company, this chief recommendation seems to be very infeasible. Although, a more depth analysis of it, more particularly in terms of finances, makes the infeasibility into a central concern for immediate solution. Other proposed recommendations are of much less value as compared to the mentioned machinery upgrade.